Genetics of cone morphology in white spruce ( Picea glauca ) - Khalil, M. A. K. (Canadian Journal of Botany, 1974)
A study was conducted in 1971 to estimate the degree of genetic control on the characters of cone morphology of white spruce (Picea glauca (Moench) Voss) from two areas of central Newfoundland and to determine whether these characters were associated with phenotypic superiority in growth. Hierarchical sampling was done, selecting two locations, two populations at each location, five trees in each population, and 20 cones from each tree. Ten characters were studied. Statistical analysis techniques used were calculation of repeatability as an estimate of heritability, hierarchical analysis of variance, and comparison of the populations of "ordinary" and "plus" trees, using Student's ‘t’ and Snedecor's 'F' tests.The results indicate that most of the 10 characters studied are under strong genetic control but these characters are not associated with phenotypic superiority in growth.